What makes news newsworthy? - Tony White (Freedom from Fear, 2009)
In order to provide counter piracy support in the Gulf of Aden, and to ensure the delivery of the Humanitarian Aid intended to the territory of Somalia, NATO escorted World Food Program vessels off the coast of Somalia, from October to December 2008. This mission was assigned to the NATO Standing Maritime Group 2 and was acting under the name of Operation Allied provider. Following the request of the Secretary General of the United Nations on 25 September 2008, the operation took place in support of UNSC resolution 1814,1816, and 1838.